miR-338-3p inhibits the invasion of renal cell carcinoma by downregulation of ALK5 - Zhang, Xiaoqian (Oncotarget, 2017)
BACKGROUND: The current study aims to elucidate the role of miRNA-338-3p (miR-338-3p) in the invasion of renal cell carcinoma (RCC). METHODS: Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed to detect the expression of miR-338-3p in human RCC cell lines with high metastatic potential (Caki-1) and low metastatic potential (786-O), respectively. The Caki-1 and 786-O cells were transfected with miR-338-3p mimic or inhibitor. Wound healing assay, Transwell assay and western blotting were performed to analyze the invasive ability and expression of activin receptor-like kinase 5 (ALK5) in the RCC cell lines. During the 36-month follow-up, we detected the expressions of miR-338-3p and ALK5 in 22 RCC cases with metastasis and 60 cases achieving a remission. RESULTS: miR-339-3p was significantly downregulated in the Caki-1 cells as compared with the 786-O cells. The transfection with miR-338-3p inhibitor caused an increased invasive ability of both two cell lines. However, the transfection with miR-338-3p mimic caused a reduction of the invasiveness. In RCC cells, the expression of ALK5 was negatively correlated to miR-338-3p. Upregulation of ALK5 partially counteracted the miR-338-3p-induced invasiveness of RCC cells. We subsequently found the negative correlations between miR-338-3p and metastasis/ALK5 expression could be also observed in human RCC tissues. CONCLUSION: Taken together, these results indicate that miR-338-3p acts as a novel tumor suppressor to inhibit the invasion of RCC by regulating ALK5 expression.